2021
DOI: 10.1002/pssb.202100275
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Site Selection and Thermoelectric Performance‐Enhancing Mechanism of Cu12Sb4S13 Doped with Pb/Ge/Sn

Abstract: Tetrahedrite Cu12Sb4S13 has attracted much attention as an earth‐abundant and ecofriendly thermoelectric material with intrinsic low thermal conductivity. Herein, the effects of carbon group elements Pb, Ge, and Sn on the electronic structure and thermoelectric properties of Cu12Sb4S13 are extensively investigated based on first‐principles electronic structure calculations and Boltzmann transport theories. It is found that the most energetically favorable sites for the elements Pb and Ge are the Cu(1) sites, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It was observed that the Ga‐4 s orbitals hybridizes strongly with those of Cu‐3 d and S‐3 p , and the impurity states appear above the E F (see Figure S4, Supporting Information), which is also observed in Cu 11.5 Ge 0.5 Sb 4 S 13 and Cu 11.5 Sn 0.5 Sb 4 S 13 system. [ 33 ] The presence of impurity states can hinder the carrier transport from VB to CB, due to the annihilation between the electrons and holes. In this regard, the electrical conductivity deteriorates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the Ga‐4 s orbitals hybridizes strongly with those of Cu‐3 d and S‐3 p , and the impurity states appear above the E F (see Figure S4, Supporting Information), which is also observed in Cu 11.5 Ge 0.5 Sb 4 S 13 and Cu 11.5 Sn 0.5 Sb 4 S 13 system. [ 33 ] The presence of impurity states can hinder the carrier transport from VB to CB, due to the annihilation between the electrons and holes. In this regard, the electrical conductivity deteriorates.…”
Section: Resultsmentioning
confidence: 99%
“…[ 27 ] Its estimated carrier concentration is above 3 × 10 21 cm −3 , which is a very high compared to the optimum concentrations (10 19 –10 20 cm −3 ). [ 28 ] In previous studies, many strategies involving the chemical elements doping were proposed to tune the electronic transport [ 23–36 ] and at the same time, reduce the thermal transport properties. For instance, the ZT value of Cu 12− x M x Sb 4 S 13 ( M is Ge or Sn, x = 0.3–0.5) increases from ≈0.46 to ≈0.65 at 665 K. But because the PF decreases, only a slight improvement in ZT value is achieved.…”
Section: Introductionmentioning
confidence: 99%